Impact of myocardial injury after coronary artery bypass grafting on long-term prognosis. (9th February 2022) - Pölzl, L; Thielmann, M; Cymorek, S; Nägele, F; Hirsch, J; Graber, M; Sappler, N; Eder, J; Staggl, S; Theurl, F; Abfalterer, H; Reinstadler, S J; et al.
Abstract: Aims: The most appropriate definition of perioperative myocardial infarction (pMI) after coronary artery bypass grafting (CABG) and its impact on clinically relevant long-term events is controversial. We aimed to (i) analyse the incidence of pMI depending on various current definitions in a 'real-life' setting of CABG surgery and (ii) determine the long-term prognosis of patients with pMI depending on current definitions. Methods and results: A consecutive cohort of 2829 coronary artery disease patients undergoing CABG from two tertiary university centres with the presence of serial perioperative cardiac biomarker measurements (cardiac troponin and creatine kinase-myocardial band) were retrospectively analysed. The incidence and prognostic impact of pMI were assessed according to (i) the 4th Universal Definition of Myocardial Infarction (4UD), (ii) the definition of the Society for Cardiovascular Angiography and Interventions (SCAI), and (iii) the Academic Research Consortium (ARC). The primary endpoint of this study was a composite of myocardial infarction, all-cause death, and repeat revascularization; secondary endpoints were mortality at 30 days and during 5-year follow-up. There was a significant difference in the occurrence of pMI (49.5% SCAI vs. 2.9% 4UD vs. 2.6% ARC). The 4th Universal Definition of Myocardial Infarction and ARC criteria remained strong independent predictors of all-cause mortality at 30 days [4UD: odds ratio (OR) 12.18; 95% confidence interval (CI) 5.00–29.67; P < 0.001; ARC: OR 13.16; 95% CI 5.41–32.00; P < 0.001] and 5 years [4UD: hazard ratio (HR) 2.13; 95% CI 1.19–3.81; P = 0.011; ARC: HR 2.23; 95% CI 1.21–4.09; P = 0.010]. Moreover, the occurrence of new perioperative electrocardiographic changes was prognostic of both primary and secondary endpoints. Conclusion: Incidence and prognosis of pMI differ markedly depending on the underlying definition of myocardial infarction for patients undergoing CABG. Isolated biomarker release-based definitions (such as troponin) were not associated with pMI relevant to prognosis. Additional signs of ischaemia detected by new electrocardiographic abnormalities, regional wall motion abnormalities, or coronary angiography should result in rapid action in everyday clinical practice. Structured Graphical Abstract: Structured Graphical Abstract The definition of perioperative myocardial infarction used has a major impact on incidence and prognosis. Created with BioRender.com. Hazard ratios are given for patients with perioperative myocardial infarction (MI) according to various definitions or electrocardiogram (ECG) changes relative to those without perioperative MI or ECG changes after coronary artery bypass grafting. ARC, Academic Research Consortium; CABG, coronary artery bypass grafting; CI, confidence interval; ECG, electrocardiogram; HR, hazard ratio; SCAI, Society for Cardiovascular Angiography and Interventions.